MOTOR PERFORMANCE OF AUSTRIAN AND SLOVAK PUPILS - A COMPARATIVE ANALYSIS - Jaromír ŠIMONEK (Cluj University Press, 2022)
Introduction. Authors compare the school physical education systems in Austria and Slovakia. Material and method. A comparative analysis was performed on two samples of pupils (n=85; male 38, female 47) aged 13-14 years in two different countries - Slovakia (n=43) and Austria (n=42). They focus on motor performance of boys and girls and compare the results in 5 selected tests: Sit and Reach, Standing Broad Jump, Sit-Ups in 30 seconds, Bent Arm Hang and 10 x 5m Shuttle Run. Authors expected that difference in the number of P.E. lessons in Austria and Slovakia can influence the level of motor performance of pupils (both male and female). Since the selected Austrian school provided longer P.E. lessons (150 min per week) than the Slovak school (90 min, they expected that Austrian pupils will perform better than their Slovak peers. Results. Based on the comparison we can assume that despite the lower number of P.E. lesson, Slovak boys and girls mostly showed better motor performance than the Austrian pupils. Statistically significant differences in favour of Slovak pupils were observed in the variables Standing Broad Jump, Sit-Ups in 30 seconds, Bent Arm Hang and 10 x 5m Shuttle Run (both genders. Austrian girls registered better results only in the Bent Arm Hang test. Conclusion. Results of our survey did not validate our expectations that Austrian pupils would have showed better motor performance than their Slovak counterparts, despite the higher number of P.E. lessons in Austria. Better performance can be attributed to sedentary behaviour of Austrian adolescents and higher physical activity of Slovak pupils during their leisure time.